Historical blocking: CN 2021-12-22 (China) - Voidly (2021)
CRITICAL severity censorship detected in China. Confidence: 98%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2021-0007
Keywords: censorship; CN; censorship; critical